Long-Term Follow-Up Examination of the Internal Jugular Vein After Vessel-Sparing Implantation of a Hickman Catheter or Port Catheter - Ritz, Laura A.; Ley-Zaporozhan, Julia; von Schweinitz, Dietrich; Hubertus, Jochen (Frontiers in Pediatrics, 2019)
Introduction: Hickman-Catheter (HC) and Port-a-Cath (Port) are frequently used in pediatrics for long-term venous access. They can be inserted either percutaneously by the Seldinger technique or by surgical venous cut-down. Catheters are inserted with a vessel-sparing technique when placed in the internal jugular vein (IJV) by venous cut-down. Data are sparse regarding the vessel’s state at long-term follow-up. This study was aimed at determining outcome after vessel-sparing implantation of an HC or Port and to compare outcome with Seldinger technique. Methods: One hundred children (58 boys, 42 girls) between 33 days and 18 years of age who underwent a vessel-sparing implantation of an HC or Port in the IJV were prospectively included. All patients underwent surgical venous cut-down at a single institution. Patency and shape of the IJV were determined by ultrasound. Operation time, catheters indwelling time, drugs administered via the catheter, catheter-associated thrombus or sepsis, patient’s body mass index, coagulopathies, and surgeon’s level of training were collected from medical records. Results: Median age was 6 years at time of operation, and the median indwelling time of catheters was 271 days. Twenty-two of our patients (22%) showed relevant alterations, classified as changes that caused an altered flow pattern. These changes included high-grade stenosis or scarring in 13 patients (13%) and occlusion in 9 patients (9%). All catheters were placed in the correct vessel, and patients did not experience any operation-associated complications, such as pneumothorax, hematopericardium, or accidental puncture of the carotid artery. Statistical analysis did not reveal any specific parameter as a risk factor for relevant structural abnormalities. Discussion: In a comparison of our data to the literature, venous cut-down showed an alteration rate of 26% and a patency rate of 85%, whereas the Seldinger technique is described to cause alteration in 15%, with a patency rate of 97% and a successful placement rate of only 90.3%-91.6%. Conclusion: The indication for long-term catheter placement may determine which method is preferable. A child who is likely to need more catheters in the future might benefit from Seldinger technique. A patient undergoing chemotherapy might benefit more from the surgical venous cut-down.